Day 2 Wed, October 23, 2019 2019
DOI: 10.2118/196813-ms
|View full text |Cite
|
Sign up to set email alerts
|

Using Thixotropic Cement Slurry for Lost Circulation Control: Case History, Volga-Urals Region

Abstract: Drilling operations within the Volga-Urals oil and gas province have a history of drilling problems manifested in partial and total losses of drilling fluid. As a result of these challenges, the companies developing and operating oil and gas fields within the region encounter the following: Significant nonproductive time (NPT) losses and additional financial costs (Urdaneta et al. 2015)Low-quality casing cementing operations proven by sonic cement-bond logging (CBL)Costly remedial cementing and sidetracking or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In this sense, uncontrolled fluid loss in a recently placed cement slurry is considered one of the main responsible triggers for production problems related to gas migration in an oil well. Fomenkov et al [88] recently suggested that highly thixotropic cement slurries can be applied in that sense.…”
Section: Lost Circulation and Fluid Lossmentioning
confidence: 99%
“…In this sense, uncontrolled fluid loss in a recently placed cement slurry is considered one of the main responsible triggers for production problems related to gas migration in an oil well. Fomenkov et al [88] recently suggested that highly thixotropic cement slurries can be applied in that sense.…”
Section: Lost Circulation and Fluid Lossmentioning
confidence: 99%